PERGESERAN MAKNA KANCA WINGKING DALAM PERSPEKTIF GENERASI MILENIAL - Chasanah, Lisa Nur; Arimi, Sailal (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2024)
In Javanese culture, a woman who has become a wife is called a kanca wingking (friend at the back). Along with the rapid development of technology and information, there are social changes in society. One of them is the shifting role of kanca wingking in Javanese society. This study aims to reveal the shifting role of kanca wingking from the perspective of the millennial generation. The research uses the theory of language variation and changes to analyze the shifting meaning of kanca wingking with a focus on three variables (gender, age, and education). This research is a qualitative descriptive research. The data of this research is in the form of language collected through a questionnaire method using Google Forms. This questionnaire was limited to respondents of Javanese descent who were born and raised in the region, language, and culture of Java (East Java, Central Java, Yogyakarta). A total of 121 respondents were collected, consisting of two generations, namely generation Y and generation Z. The results showed that the shift in the meaning of kanca wingking from the perspective of the millennial generation almost completely occurred in the present. Generation Y tends to know the meaning of kanca wingking better than generation Z. The term kanca wingking is not completely abandoned but has a very different role in the household and views or perceptions among the community. The role of kanca wingking in the perspective of the millennial generation is more flexible, less rigid, and likes freedom, while the perspective or view in society tends to positively assess and support the achievements of a woman or wife.Dalam kebudayaan Jawa, perempuan yang telah berstatus menjadi seorang istri disebut dengan istilah kanca wingking (teman di belakang). Seiring perkembangan teknologi dan informasi yang semakin pesat menyebabkan adanya perubahan sosial di dalam masyarakat. Salah satunya adalah pergeseran peran kanca wingking dalam masyarakat Jawa. Penelitian ini bertujuan untuk mengungkapkan pergeseran peran kanca wingking dalam perspektif generasi milenial. Penelitian menggunakan teori variasi dan perubahan bahasa untuk menganalisis pergeseran makna kanca wingking dengan fokus pada tiga variabel (jenis kelamin, usia, dan pendidikan). Penelitian ini adalah penelitian deskriptif kualitatif. Data penelitian ini berupa bahasa yang dikumpulkan melalui metode kuesioner menggunakan Google Form. Kuesioner ini dibatasi pada responden keturunan asli Jawa yang lahir hingga besar berada di wilayah, bahasa, dan budaya Jawa (Jawa Timur, Jawa Tengah, DIY). Responden terkumpul sejumlah 121 orang yang terdiri dari atas dua generasi, yaitu generasi Y dan generasi Z. Hasil penelitian menunjukkan bahwa pergeseran makna terhadap kanca wingking dalam perspektif generasi milenial hampir sepenuhnya terjadi di masa sekarang. Generasi Y cenderung lebih mengetahui makna kanca wingking daripada generasi Z. Istilah kanca wingking tidak sepenuhnya ditinggalkan, tetapi memiliki peran yang sangat jauh perbedaannya dalam rumah tangga dan pandangan atau persepsi di kalangan masyarakat. Peran kanca wingking dalam perspektif generasi milenial lebih fleksibel, tidak kaku, dan menyukai kebebasan, sedangkan perspektif atau pandangan di dalam masyarakat cenderung menilai positif dan mendukung atas prestasi seorang perempuan ataupun istri.